Informal vs. Formal Care in Finland: Monetary Incentives and Fiscal Implications - Niku Määttänen; Tomi Salminen (The Research Institute of the Finnish Economy (ETLA), 2017)
We consider the private economic incentives and the fiscal consequences related to informal long-term care by e.g. family members and formal care in institutions. We focus on the case where providing informal care implies less market work. In such cases, informal care reduces both private wage income and government tax revenue compared to formal care. On the other hand, the cost of formal care may be borne largely by the state. We provide a detailed quantitative analysis of the Finnish case. We describe how the private economic incentives and fiscal consequences relate to the wage level of the potential informal care provider and the income of the care receiver. We find that they vary greatly across individuals. It seems likely, however, that in most cases the fiscal cost of informal care is smaller than that of formal care. The private monetary incentives, on the other hand, tend favor formal care over informal care.
Keywords: 330; Long-term care; Informal care; Public finances